Komunikasi Ritual Pada Tradisi Tumbilotohe Di Gorontalo (Studi Fenomenologi Pelaksanaan Tumbilotohe Di Kelurahan Ipilo) - Deu, Reffli; Dano Putri, Citra F.I.L; Thomas, Abdul wahab (JAMBURA JURNAL ILMU KOMUNIKASI, 2024)
The Tumbilotohe tradition in Gorontalo, which serves as a cultural identity for the community, has changed with the shift from traditional bottle lamps to modern electric lights. This transition has sparked debates regarding its impact on the meaning and sacredbess of the tradition.The findings indicate that ritual communication in the tumbilotohe tradition is vital for preserving the tradition’s meaning amids changes, such as adopting modern decorative lights. The role of traditions leaders in harmonizing the understanding between organizers and the community is crucial to ensuring that the essense and intergrity of the tumbilothe tradition are maintained despite these changes.